PERLINDUNGAN KONSUMEN JASA KEUANGAN PASCA PEMBENTUKAN OTORITAS JASA KEUANGAN (OJK) - Inosentius Samsul (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2013)
Consumer Protection in Indonesia experienced significant growth after the enacment of Act No. 8 of 1999 on Consumer Protection as umbrella of the consumer protection laws. Act No. 21 of 2011 on the Financial Services Authority as part of consumer protection laws. This paper aims to analyze the two problems, the first is relationship of the consumer protection Act No. 8 of 1999 (CP Act) and Act No. 21 of 2011concerning the Financial Services Authority (FSA Act). Second, to analyze the vertical synchronization between the Act No. 21 of 2011 on the Financial Services Authority with the Financial Services Authority Regulation No.1 Year 2013 on Consumer Protection Financial Services Sector as the implementation regulation of the FSA Act. Analysis of the first problem is the complementary relationship between the Act 8 of 1999 and Act No. 21 of 2011. Act No. 21 of 2011 strengthen consumer protection laws on the financial services sectors. Second, FSA regulation No. 1 of 2013 a detailed set of consumer protection efforts. But there are still some substances that has not been spelled out in the regulation. There are some substances of the Financial Services Authority Act no further stipulated in the FSA regulation. Therefore, the important suggestion of this paper is the implementation of some provisions of the Act No 21 of 2011 should be in line with Act No 8 of 1999 to strengthen consumer protection system in Indonesia. In addition, the FSA should issue a separate regulation of the legal defense that has not been accommodated in the FSA Regulation No. 1 of 2013.ABSTRAKPerlindungan Konsumen di Indonesia mengalami perkembangan yang cukup signifikan setelah terbentuknya Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen sebagai payung hukum perlindungan konsumen. Undang-Undang No. 21 Tahun 2011 tentang Otoritas Jasa Keuangan sebagai bagian dari hukum perlindungan konsumen. Tulisan ini bertujuan untuk menganalisis 2 (dua) permasalahan, yaitu pertama hubungan perlindungan konsumen dalam Undang-Undang No. 8 Tahun 1999 dan UU No. 21 Tahun 2011. Kedua, menganalisis sinkronisasi vertikal antara Undang-Undang No. 21 Tahun 2011 tentang Otoritas Jasa Keuangan dengan Peraturan Otoritas Jasa Keuangan No. 1 Tahun 2013 tentang Perlindungan Konsumen Sektor Jasa Keuangan. Analisis terhadap permasalahan pertama adalah mengenai hubungan komplementer antara Undang-Undang No. 8 Tahun 1999 dan UU No. 21 Tahun 2011. Undang-Undang Nomor 21 Tahun 2011 memperkuat hukum perlindungan konsumen sektor jasa keuangan. Kedua, peraturan OJK No. 1 Tahun 2013 mengatur secara rinci tentang upaya perlindungan konsumen. Namun masih terdapat substansi yang belum dijabarkan dalam peraturan tersebut. Ada beberapa materi dalam Undang-Undang tentang Otoritas Jasa Keuangan yang tidak daitur lebih lanjut dalam peraturan tersebut. Oleh karena itu, saran penting dari tulisan ini adalah pelaksanaan dari beberapa ketentuan dalam UU No. 21 Tahun 2011 haruslah sejalan dengan Undang-Undang Nomor 8 Tahun 1999 untuk memperkuat sistem perlindungan konsumen di Indonesia. Di samping itu, OJK perlu mengeluarkan peraturan tersendiri mengenai pembelaan hukum yang belum terakomodasi dalam Peraturan OJK Nomor 1 Tahun 2013.